(untitled) (REMUNOM, 2024)
This work analyzes the mental health of offshore workers from a nursing perspective. This problem consists of understanding how extreme working conditions, such as long working hours, geographic isolation and exposure to physical and psychological risks, impact the mental health of these professionals. The relevance of this issue is imposed by the need to improve understanding and intervention in mental health in the offshore environment. The central objective of this study is to evaluate the mental health of offshore workers, identify the main prevalent mental disorders and propose effective intervention strategies. For this, a methodological approach was used that includes literature review and analysis of data collected from previous studies. The Google Academic, LILACS and SciELO databases were consulted to obtain relevant and updated references. The research was based on a bibliographical review and analysis of existing nursing practices. The analysis showed that disorders such as stress, anxiety and depression are significantly prevalent among offshore workers. It was concluded that nursing practices play a crucial role in managing and supporting the mental health of these workers, highlighting the need for more effective strategies and a more robust commitment to mental health programs in the offshore environment. The conclusion of the study reinforces the importance of continuous and specific interventions to improve workers’ mental health and quality of life, suggesting the implementation of more effective and integrated occupational health policies.